2019
DOI: 10.22603/ssrr.2018-0106
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Produced by Osteoclasts Might Induce Intractable Pain in a Rat Spinal Metastasis Model of Breast Cancer

Abstract: Introduction Causes of pain due to spinal metastases have been insufficiently investigated. Tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were the focus of this study. Both are known as proinflammatory cytokines associated with the pathophysiology of pain syndromes 1 ) . It is well known that cancer cells produce these cytokines, but whether osteoclasts produce them as well remains unclear. We hypothesize that osteoclasts produce these cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Mazaki et al (2019) performed a real-time PCR test to samples taken from mice vertebrae with breast cancer metastases, proving an increase in TNF-α gene expression compared to IL-6, and this was in line with the results of immunohistochemical expression. It is evident that TNF-α affects lytic lesions in bone metastases [35]. Takahashi et al (2003) studied 29 cancer patients with hypercalcemia and found that TNF-α levels in serum increased, though not significantly [36].…”
Section: Tnf-α Expression In Bone Metastatic Hypercalcemiasupporting
confidence: 65%
See 1 more Smart Citation
“…Mazaki et al (2019) performed a real-time PCR test to samples taken from mice vertebrae with breast cancer metastases, proving an increase in TNF-α gene expression compared to IL-6, and this was in line with the results of immunohistochemical expression. It is evident that TNF-α affects lytic lesions in bone metastases [35]. Takahashi et al (2003) studied 29 cancer patients with hypercalcemia and found that TNF-α levels in serum increased, though not significantly [36].…”
Section: Tnf-α Expression In Bone Metastatic Hypercalcemiasupporting
confidence: 65%
“…Correspondingly, serum TNF-α levels were proven to have a positive correlation with high invasion of cancer cells to bone and poor patient prognosis [34]. Mazaki et al (2019) performed a real-time PCR test to samples taken from mice vertebrae with breast cancer metastases, proving an increase in TNF-α gene expression compared to IL-6, and this was in line with the results of immunohistochemical expression. It is evident that TNF-α affects lytic lesions in bone metastases [35].…”
Section: Tnf-α Expression In Bone Metastatic Hypercalcemiamentioning
confidence: 62%
“…However, in order to evaluate the main contributors involved in IL-6 expression during breast cancer bone metastases, numerous in vitro and in vivo studies analyzed tumor cells, bone cells, immune cells, and the organic bone matrix. Several preclinical studies showed that metastatic breast cancer cells, directly [54][55][56][57][58][59] or through Jagged1-expressing tumor cells [58], induced osteoblasts to express high levels of IL-6 [54][55][56][57][58][59][60][61], while they seemed to not affect IL-6 production by osteoclasts [62,63]. The high expression of IL-6 by osteoblasts, particularly activated throughout the bone marrow [60], completely suppresses osteoblast functions [55] and stimulates osteoclastogenesis in the presence or absence of the receptor activator of nuclear factor kappa-B (RANK)/RANK ligand (RANKL) pathway [56,59].…”
Section: Il-6mentioning
confidence: 99%